Practices, knowledge, and concerns for out-of-home firearm storage among those with access to firearms: results from a survey in two states - Leslie M. Barnard; Rachel L. Johnson; Sara Brandspigel; Lauren A. Rooney; Megan McCarthy; Frederick P. Rivara; Ali Rowhani-Rahbar; Christopher E. Knoepke; Ryan A. Peterson; Marian E. Betz (BMC, 2023)
Abstract Background Temporary, voluntary storage of firearms away from the home is a recommended option for individuals with risk of suicide, but it may also be used in other situations (e.g., long trips). Prior work has explored the availability of storage options and the views of storage locations. Little is known about out-of-home storage practices among those who live in homes with firearms (including owners). Methods We surveyed English-speaking adults (18 or older) in two states (Colorado and Washington) living in a home with a firearm (June-July 2021). Results Among the final sample of 1029, most respondents were white (88.1%) and non-Hispanic (85.0%); half were female (50.8%), and the most common age group was ages 35-44 (25.5%). Just over one quarter (27.3%) of respondents indicated they had stored a firearm away from their home/car/garage in the last 5 years. The place most respondents said they were somewhat or very likely to consider was at a family members home (62.7%) or at a self-storage facility (52.5%). Conclusion Out-of-home firearm storage is a relatively common practice and endorsed by many gun-owners, suggesting out-of-home storage is feasible for firearm owners as an approach to suicide prevention.